REKOMENDASI FRAMEWORK PHP DALAM PENGEMBANGAN WEBSITE BISNIS MENGGUNAKAN METODE AHP DAN SAW - Agustina, Fitria Rahma; Muflihah, Yusrida (LPPM Universitas Bina Bangsa, 2024)
This research aims to compare and apply the Analysis of Hierarchical Process (AHP) and Simple Additive Weighting (SAW) methods in a Decision Support System (SKS) to select the optimal PHP framework for business website development. AHP is used to evaluate relevant criteria in selecting a framework, such as performance, security, scalability, and community support. On the other hand, SAW is used to assign weights to each criterion and calculate the relative value of each PHP framework alternative. This research compares the two methods in the context of selecting a suitable PHP framework for business website development. The assessment is conducted using data from practical experience and mathematical analysis to assess the performance and advantages and disadvantages of each method. Hopefully, this comparison can provide a deeper understanding of the optimal use of AHP and SAW in selecting a PHP framework. The implementation of this SDM is expected to help developers and business owners to choose the optimal PHP framework according to their preferences and project needs. The advantage of this approach is its ability to reduce uncertainty in decision making and provide a better understanding of the preferences underlying the PHP framework selection process